The Neisseria meningitidis outer membrane lipoprotein FrpD binds the RTX protein FrpC - Prochazkova, Katerina; Osicka, Radim; Linhartova, Irena; Halada, Petr; Sulc, Miroslav; Sebo, Peter (The Journal of biological chemistry, 2005)
At conditions of low iron availability, Neisseria meningitidis produces a family of FrpC-like, type I-secreted RTX proteins of unknown role in meningococcal lifestyle. It is shown here that iron starvation also induces production of FrpD, the other protein expressed from a gene located immediately upstream of the frpC gene in a predicted iron-regulated frpDC operon. We found that FrpD is highly conserved in a set of meningococcal strains representative of all serogroups and does not exhibit any similarity to known sequences of other organisms. Subcellular localization and [3H]palmitic acid labeling in Escherichia coli revealed that FrpD is synthesized with a type II signal peptide for export across the cytoplasmic membrane and is, upon processing to a lipoprotein, sorted to the outer bacterial membrane. Furthermore, the biological function of FrpD appears to be linked to that of the RTX protein FrpC, because FrpD was found to bind the amino-proximal portion of FrpC (first 300 residues) with very high affinity (apparent Kd approximately 0.2 nM). These results suggest that FrpD represents an rtx loci-encoded accessory lipoprotein that could be involved in anchoring of the secreted RTX protein to the outer bacterial membrane.
Keywords: Conserved Sequence; Iron; Protein Binding; Bacterial Outer Membrane Proteins; proteiny vnější bakteriální membrány; Molecular Sequence Data; Bacterial Proteins; terciární struktura proteinů; sekvence aminokyselin; vápník; Base Sequence; Protein Structure, Tertiary; lipoproteiny; Calcium; vazba proteinů; sekvence nukleotidů; Lipoproteins; železo; Membrane Proteins; membránové proteiny; Amino Acid Sequence; Neisseria meningitidis; konzervovaná sekvence; molekulární sekvence - údaje; bakteriální proteiny